Physical modeling of ski-jump spillway to evaluate dynamic pressure - Moghadam M.K.; Amini A.; Malek M.A.; Mohammad T.; Hoseini H. (MDPI AG, 2023)
Energy dissipation; Ski jumps; Dynamic pressures; Initial thickness; Physical model; Pressure fluctuation; Reduced dynamics; Ski-jump bucket; Surface disturbances; Water jets; Dynamics; disturbance; energy dissipation; laboratory method; modeling; physical method; pressure